2022
DOI: 10.3389/fsufs.2021.782425
|View full text |Cite
|
Sign up to set email alerts
|

Biocontrol of Anthracnose Disease on Chili Pepper Using a Formulation Containing Paenibacillus polymyxa C1

Abstract: Anthracnose disease on chili pepper has been known to seriously interfere with the plant growth and obviously reduce the yield. The disease is caused by Colletotrichum spp. In Bali, Indonesia, six species of Colletotrichum have been identified: Colletotrichum scovillei, C. acutatum, C. nymphaeae, C. gloeosporioides, C. truncatum, and C. fructicola. However, among them the C. scovillei was found to be the most prevalent cause of anthracnose on chili pepper in Bali. Two species of antagonist against C. scovillei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…On the other hand, the GYUN-2311 treatment has shown the disease rate of 36.18% which is similar to TK ® treatment with disease rate of 37.52%. In support of our findings, Suprapta (2022) provided evidence that the application of Paenibacillus polymyxa C1 successfully reduced the occurrence of anthracnose incidence in chili peppers under greenhouse conditions by 30.38–97.34% subsequent to treatment with different formulations, as compared to the control group ( p < 0.05). Several Bacillus species have been reported to reduce the severity of disease on a range of hosts ( Kim et al, 2012 ; Lee et al, 2013 ).…”
Section: Discussionsupporting
confidence: 86%
“…On the other hand, the GYUN-2311 treatment has shown the disease rate of 36.18% which is similar to TK ® treatment with disease rate of 37.52%. In support of our findings, Suprapta (2022) provided evidence that the application of Paenibacillus polymyxa C1 successfully reduced the occurrence of anthracnose incidence in chili peppers under greenhouse conditions by 30.38–97.34% subsequent to treatment with different formulations, as compared to the control group ( p < 0.05). Several Bacillus species have been reported to reduce the severity of disease on a range of hosts ( Kim et al, 2012 ; Lee et al, 2013 ).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the mushroom culture filtrate, Clitocybe nuda (LA82), effectively reduced the severity of anthracnose disease (Chen and Huang, 2010). Suprapta (2022) found that the formulation of Paenibacillus polymyxa C1 effectively controlled the anthracnose disease under field conditions.…”
Section: Effect Of Antagonistic Activity On C Capsici Severity Determ...mentioning
confidence: 97%
“…The bacterial isolates were transferred with an ose needle to the PDA media and incubated at 27 ± 2 • C for 3 days. Fermentation (room temperature 28-30 • C ) of P. caninum leafs extract: a mixture of 20 mg of P caninum extract, 1 one liter of potato boiled water, and 1 ml suspension of B. agri was transferred into a glass bottle and incubated for 30 days at 27 ± 2 • C) before application to rice plants (Suprapta, 2022).…”
Section: Production Of B Agrimentioning
confidence: 99%